Low power networks-on-chip - Silvano, Cristina; Lajolo, Marcello; Palermo, Gianluca (Springer, 2011)
Low Power Networks-on-Chip Edited by: (editors) Cristina Silvano Marcello Lajolo Gianluca Palermo In recent years, both Networks-on-Chip, as an architectural solution for high-speed interconnect, and power consumption, as a key design constraint, have continued to gain interest in the design and research communities, since power and energy issues still represent one of the limiting factors in integrating multi- and many-cores on a single chip. This book covers power and energy aware design techniques from several perspectives and abstraction levels and offers a single-source reference to some of the most important design techniques proposed in the context of low-power design for networks-on-chip architectures. ?Describes the most important design techniques that were invented, proposed, and applied to reduce both dynamic power and static power dissipation in networks-on-chip based architectures; ?Applies state-of-the-art, low-power design techniques to the design of Networks-on-Chip, to demonstrate methodology for design of high-speed, low-power interconnect; ?Offers a single source reference to the latest research, otherwise available only in disparate journals and conference proceedings.